STUDIES ON SUMMER MASTITIS IN COWS IN IRAQ - Yass, A. A.; wdish, I; A. H., Judi (The Iraqi Journal of Veterinary Medicine, 1996)
A total of two-hundred and thirty-two cows (eight hundred and eighty four milk samples) located in three different regions in Iraq were examined the overall incidence of summer mastitis was found to be 6.90% (4.98% on quarter basis). The udder infections were highest during August (47.73%) and September (27.27%). Bacteriological examination of milk samples revealed that C. pyogenes (35.18%) were the main etiological agents followed by Str. agalactiae (22.22%) Str. dysagalatiae (16.67%), Str. uberis (9.26%), Staph. aureus (7.41%) and Microcoeeus indolicus (5.56%). The In vitro sensitivity testing of mastitis pathogens, showed that all isolates (100%) tested were sensitive to gentamycin. Most isolates (77.78 to 87.04% of the isolates) were sensitive to erythromycin, kanamycin, oxytetracycline and chloramphenicol.